2022
DOI: 10.1007/s11042-022-14165-4
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Diabetic Retinopathy using Convolutional Neural Networks for Feature Extraction and Classification (DRFEC)

Abstract: Diabetic Retinopathy (DR) is caused as a result of Diabetes Mellitus which causes development of various retinal abrasions in the human retina. These lesions cause hindrance in vision and in severe cases, DR can lead to blindness. DR is observed amongst 80% of patients who have been diagnosed from prolonged diabetes for a period of 10–15 years. The manual process of periodic DR diagnosis and detection for necessary treatment, is time consuming and unreliable due to unavailability of resources and expert opinio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(8 citation statements)
references
References 78 publications
0
8
0
Order By: Relevance
“…Among the three models, ResNet50 produced the best classification accuracy. On the contrary, in separate research [32], Das et al found that ResNet50 is the most overfitted model among the 26 state-of-the-art deep learning models. According to the experiments, EfficientNetB4 is the most optimal model for DR classification, followed by Inception-ResNet-v2 and NASNetLarge in the second and third positions, respectively.…”
Section: Related Workmentioning
confidence: 96%
“…Among the three models, ResNet50 produced the best classification accuracy. On the contrary, in separate research [32], Das et al found that ResNet50 is the most overfitted model among the 26 state-of-the-art deep learning models. According to the experiments, EfficientNetB4 is the most optimal model for DR classification, followed by Inception-ResNet-v2 and NASNetLarge in the second and third positions, respectively.…”
Section: Related Workmentioning
confidence: 96%
“…The model built in [14] can be implemented as a mobile application to support doctors in the treatment of patients with diabetic retinopathy. A complex model using several models of neural networks is proposed in [15]. In [16] and [17], the advantages of the DenseNet architecture in determining the degree of diabetic retinopathy are given.…”
Section: Fig 1: Comparison Between Normal and Diabetic Retinal Images...mentioning
confidence: 99%
“…By studying the style classification of ink painting works [1][2], we can gain a deeper understanding of the historical background, creative motivation, and artistic techniques of these art works, providing more accurate and comprehensive information and analysis for art history and cultural research [3]. Therefore, the background and significance of studying the style classification of ink painting works lies in inheriting and protecting traditional art, promoting the development of art history and cultural research, and enhancing people's understanding and appreciation of traditional art.…”
Section: Introductionmentioning
confidence: 99%